A reflective learning report about the implementation and impacts of Psychological First Aid (PFA) in Gaza. Issue 1 (2nd January 2016) - Schafer, Alison; Snider, Leslie; Sammour, Rania
Abstract: Psychological First Aid (PFA) is the recommended immediate psychosocial response during crises. As PFA is now widely implemented in crises worldwide, there are increasing calls to evaluate its effectiveness. World Vision used PFA as a fundamental component of their emergency response following the 2014 conflict in Gaza. Anecdotal reports from Gaza suggest a range of benefits for those who received PFA. Though not intending to undertake rigorous research, World Vision explored learnings about PFA in Gaza through Focus Group Discussions with PFA providers, Gazan women, men and children and a Key Informant Interview with a PFA trainer. The qualitative analyses aimed to determine if PFA helped individuals to feel safe, calm, connected to social supports, hopeful and efficacious – factors suggested by the disaster literature to promote coping and recovery (Hobfoll et al., 2007). Results show positive psychosocial benefits for children, women and men receiving PFA, confirming that PFA contributed to: safety, reduced distress, ability to engage in calming practices and to support each other, and a greater sense of control and hopefulness irrespective of their adverse circumstances. The data shows that PFA formed an important part of a continuum of care to meet psychosocial needs in Gaza and served as a gateway for addressing additional psychosocial support needs. A "whole-of-family" approach to PFA showed particularly strong impacts and strengthened relationships. Of note, the findings from World Vision's implementation of PFA in Gaza suggests that future PFA research go beyond a narrow focus on clinical outcomes, to a wider examination of psychosocial, familial and community-based outcomes.